Pengaruh Konsumsi Kunyit Asam (Curcuma domestic tamarindus indica) Terhadap Tingkat Nyeri Disminorhea Ramaja Putri - Nisa, Setia; Armalini, Rika (JUKEJ : Jurnal Kesehatan Jompa, 2024)
A reproductive health report from the World Health Organization (WHO) states that almost 85% of women of childbearing age experience dysmenorrhea during menstruation, 70% of which are in the age group of 13 - 21 years. during menstruation, 70% of whom are in the age group of 13 - 21 years. RISKESDAS data from the Ministry of Health Republic of Indonesia, the incidence of dysmenorrhea is 65.4% of the total women of of childbearing age and 78.6% are early adolescents. The purpose of this study was to determine the effect of turmeric consumption. Sour Turmeric (Curcuma Domestica Tamarindus Indica) on the Pain Level of Dysmenorrhea in Adolescent Girls at the Air Santok Health Center, Pariaman City. Type of This research is a quasiexperimental designs. Location The research was conducted at the Air Santok Health Center in Pariaman City and was conducted in October 2024. The population of all adolescent girls at Puskesmas Air Santok Pariaman City who experienced dysminorhea in the last 3 months was 22 people. The results showed the respondent's pain level before (Pretest) was done Most of the consumption of sour turmeric is in the moderate category, with a mean value of 5.68. The pain level of respondents after (Postest) is done The majority of the consumption of sour turmeric is in the mild category, with a mean value of 3.18. There is an effect of consumption of sour turmeric with pain levels in female students at the Air Health Center Santok Pariaman City in 2024 with a p value of 0.001 It is expected that adolescents who experience dysmenorrhea to consume turmeric acid as an alternative treatment to reduce pain, because in addition to being safe, the ingredients needed are also easily available.